DAKWAH ERA DIGITAL: PROBLEMATIKA DAN METODE DAKWAH MEDIA MASSA - Intan Wulansari; Daud Rasyid; Dewi Nurani; Abdullah Ghulam Nazih; Hayati Hayati; Satimah Satimah (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2025)
Dakwah through mass media has become a key strategy in spreading Islamic teachings to a wide audience. Advances in information technology have enabled preachers to reach the public quickly and efficiently, especially through platforms such as television, radio, and social media. The purpose of this study is to identify problems in preaching and appropriate methods when preaching using digital-based mass media. The research method used is a literature review, a research method that involves searching, collecting, and analyzing secondary data sources such as books, journals, and other documents. The results of the study show that varying levels of religious understanding among the public also affect the acceptance of da'wah messages, requiring preachers to deliver material that is relevant and easily understood by various groups. Commercial pressures are an additional obstacle, as the mass media often prioritizes content that is more financially profitable over da'wah content, which is generally educational and serious in nature. The proposed solutions to overcome these challenges include the use of a contextual approach, adaptation of communication styles, segmentation of mad'u, and professionalization of da'wah through technology training. With this strategy, da'wah through the mass media can meet the needs of modern society without sacrificing the essence of Islamic teachings